Political Economy of Indonesia’s Free Nutritious Meal Policy: Governance and Institutional Analysis - Cik Ida Kumalasari Amirudin; Romy Hermawan (IJBAMS: International Journal of Business Accounting Management Social Science, 2026)
This study examines the political economy of Indonesia’s Free Nutritious Meal (FNM) policy under President Prabowo Subianto, focusing on governance arrangements and institutional capacity in managing large-scale public expenditure. The research problem addresses how fiscal allocation, institutional coordination, and policy legitimacy interact in the formulation and implementation of the FNM program. Using a qualitative case study design, this research analyzes official government documents, budget reports, regulatory frameworks, and secondary academic sources published between 2023 and 2025. Descriptive fiscal analysis indicates that the projected annual allocation for the program accounts for a significant proportion of the national social expenditure budget, exceeding IDR 400 trillion in initial policy projections (Ministry of Finance, 2024). Findings reveal three key results. First, the policy reflects distributive political priorities embedded in the national budgeting process. Second, institutional readiness varies across implementing agencies, indicating coordination challenges between central and local governments. Third, public support for the program is strongly associated with welfare framing and food security narratives. The study concludes that the FNM policy represents not only a social welfare intervention but also a strategic fiscal instrument shaped by political-economic considerations. Its long-term sustainability depends on institutional capacity, fiscal discipline, and transparent governance mechanisms.